Sweat-traceless ammonia-free elastic polyester and preparation method thereof
By introducing hydrophilic groups and modifiers in polyester fibers, combined with hygroscopic sweats and polyurethane tidal agents, the problem of insufficient performance of traditional polyester fiber hygroscopic sweats and may cause skin allergies. The efficient and hygroscopic perspiration effect of marks and ammonia.
Patent Information
- Application Number
- CN202411475882.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional polyester fibers have shortcomings in moisture-absorbing and sweating properties, which are prone to sweat marks, and the spandex added to some polyester fibers during the manufacturing process may cause skin allergies.
Using the synergistic effect of hydrophilic polyester fiber, moisture-wicking finishing agent and polyurethane finishing agent, by introducing hydrophilic groups and modifiers, the moisture-wicking performance of polyester is improved, the appearance of sweat marks is reduced, and through the polyurethane Finishing agents improve the durability and stability of fabrics.
It effectively improves the moisture absorption and perspiration performance of polyester, reduces the appearance of sweat marks, improves wearing comfort and aesthetics, and avoids skin allergies caused by the use of spandex.
Smart Images

Figure BDA0005096093820000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of textile technology, and in particular to a sweat-free, spandex-free elastic polyester and a preparation method thereof. Background Art
[0002] As a representative of synthetic fibers, polyester has been widely used in the textile industry due to its excellent physical properties and durability. Polyester fibers not only have high strength and wear resistance, but also have good wrinkle resistance, easy to wash and quick drying. Especially in the fields of sportswear, outdoor equipment, etc., the application of polyester fibers has played an important role in improving wearing comfort and protective performance.
[0003] However, as consumers' demands for clothing comfort and health continue to increase, the performance of traditional polyester fibers in some aspects can no longer fully meet the demand. Traditional polyester fibers are insufficient in terms of moisture absorption and perspiration wicking performance, and are prone to sweat marks, which affects wearing comfort. At the same time, in order to meet the elasticity requirements, some polyester fibers are added with elastic components such as spandex during the manufacturing process, but these components may cause skin allergies and other problems. Therefore, it is necessary to develop a polyester fabric that is sweat-free and free of spandex. Summary of the invention
[0004] In order to reduce the appearance of sweat marks on polyester fabrics, the present application provides a sweat-free, spandex-free elastic polyester and a preparation method thereof.
[0005] The present application provides a sweat-free, non-spandex polyester and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides a sweat-free and non-spandex polyester, which adopts the following technical solution: A sweat-free and non-spandex polyester, the raw materials for preparing which include the following components in parts by weight: 4-6 parts of hydrophilic polyester fiber 0.5-0.8 parts of moisture wicking finishing agent 0.4-0.6 parts of polyurethane finishing agent.
[0006] Hydrophilic polyester fiber improves the problem of poor moisture absorption of traditional polyester. By introducing hydrophilic groups, it can quickly absorb sweat discharged from the human body, keeping the skin dry and comfortable at all times, greatly improving the comfort of wearing; the moisture wicking finishing agent works synergistically with the hydrophilic polyester fiber to efficiently absorb moisture and promote the rapid diffusion and evaporation of sweat, prevent sweat residue, reduce bacterial growth and odor generation, and reduce the appearance of sweat marks; the polyurethane finishing agent can cross-link with the fabric fiber, and cover the film layer on the basis of the moisture wicking finishing agent, further improving the durability and stability of sweat-free and spandex-free polyester, making the fabric smooth and comfortable; through the synergistic effect of hydrophilic polyester fiber, moisture wicking finishing agent and polyurethane finishing agent, the moisture wicking performance of polyester is effectively improved, the appearance of sweat marks is reduced, and the aesthetics and comfort of wearing are improved.
[0007] Preferably, the raw materials for preparing the hydrophilic polyester fiber include citric acid, polyethylene glycol and sodium 5-sulfonisophthalate.
[0008] Citric acid molecules contain multiple carboxyl and hydroxyl groups, which can form hydrogen bonds with water molecules to enhance the hydrophilicity of the fiber; polyethylene glycol molecular chains are rich in ether bonds, which can form hydrogen bonds with water molecules, thus giving the fiber good hygroscopicity. The fiber can quickly absorb sweat and keep the skin surface dry; the sulfonic acid group in sodium 5-sulfonate isophthalic acid provides ionicity for the fiber, increases the affinity of the fiber for water molecules, and can form a hydration layer through ionic interactions, further improving the fiber's moisture absorption capacity. Sweat is quickly conducted to the fiber surface through the capillary action between the fibers, accelerating the evaporation of sweat, thereby improving the moisture absorption and perspiration performance.
[0009] Preferably, the mass ratio of citric acid, polyethylene glycol and 5-sodium sulfoisophthalate is (0.024-0.048):1:0.65.
[0010] The hydrophilic polyester fiber prepared according to the above mass ratio has good hydrophilicity and moisture absorption and perspiration removal properties.
[0011] Preferably, the hydrophilic polyester fiber is prepared by the following steps: The citric acid, polyethylene glycol and catalyst are heated until they are melted, and after obtaining a molten mixture, stirring is started, and a heat stabilizer is added after heat preservation, and the temperature is increased for reaction, and the water is evaporated and the temperature is maintained, and xylene and 5-sodium sulfoisophthalate are added after cooling, and the temperature is increased for reaction again, and then a vacuum distillation reaction is carried out at a constant temperature. After the reaction is completed, the temperature is reduced and the material is discharged to obtain a hydrophilic polyester; The hydrophilic polyester and tetrabutylammonium bromide prepared above are dispersed in N,N-dimethylformamide to obtain a spinning solution, and the spinning solution is subjected to electrostatic spinning to obtain hydrophilic polyester fibers.
[0012] The hydrophilic polyester fiber prepared according to the above steps has good hydrophilicity and moisture absorption and perspiration resistance. The addition of tetrabutylammonium bromide can significantly improve the conductivity of the spinning solution, thereby promoting the formation of multiple fine branches in the spinning jet, so that the fiber forms a branched structure, and the porosity of the fiber is improved, thereby improving the moisture absorption and perspiration resistance of the polyester.
[0013] Preferably, the raw materials for preparing the moisture absorption and perspiration finishing agent include a surface modifier, a wall material and a core material.
[0014] Preferably, the raw materials for preparing the surface modifier include N,N-diethyl-2-acrylamide, trifluoroethyl methacrylate and vinyl tri(β-methoxyethoxy)silane.
[0015] N, N-diethyl-2-acrylamide has an amide group, has good hydrophilicity and temperature sensitivity, can undergo a conformational transformation when the temperature rises, becoming more hydrophilic, and repellent at low temperatures, thereby improving the moisture absorption and perspiration resistance of the fabric and wearing comfort; the trifluoroethyl group of trifluoroethyl methacrylate has low surface energy, which can improve the hydrophobic and stain-resistant properties of the fabric, thereby improving wearing comfort; vinyl tri(β-methoxyethoxy) silane has a volume-increasing effect, and the siloxane structure can condense with the hydroxyl groups on the fiber surface after hydrolysis, thereby enhancing the bonding force between the moisture absorption and perspiration finishing agent and the fiber surface, thereby improving the stability and durability of the sweat-free and spandex-free polyester.
[0016] Preferably, the mass ratio of N,N-diethyl-2-acrylamide, trifluoroethyl methacrylate and vinyl tri(β-methoxyethoxy)silane is 1:(0.27-0.53):0.48.
[0017] The surface modifier prepared according to the above mass ratio has a good modification effect, and the prepared moisture absorption and perspiration finishing agent has good moisture absorption and perspiration performance and hydrophobic and stain resistance.
[0018] Preferably, the raw materials for preparing the wall material include styrene and tetrabutyl titanate.
[0019] Styrene is polymerized in situ on the surface of the core material to obtain polystyrene, which is used to preliminarily embed the core material. Tetrabutyl titanate generates mesoporous titanium dioxide in situ on the surface of polystyrene to reinforce the inner wall material and encapsulate the core material more stably. Titanium dioxide has good antioxidant properties and can improve the durability of the fabric. The rich pore structure can promote the improvement of moisture absorption and perspiration performance, while also improving the hydrophobicity and stain resistance.
[0020] Preferably, the core material comprises n-octadecane.
[0021] n-Octadecane has good heat storage and heat release properties, and can regulate the temperature of the fiber to a certain extent. It can work synergistically with wall materials and surface modifiers to accelerate the evaporation of sweat, increase the drying speed, and enhance the wearing comfort of the fabric.
[0022] In a second aspect, the present application provides a method for preparing sweat-free and non-spandex polyester, using the following technical solution: A method for preparing sweat-free and spandex-free polyester comprises the following steps: The hydrophilic polyester fiber is woven to obtain a hydrophilic polyester fabric, a moisture absorption and perspiration-releasing finishing agent is dispersed in deionized water to obtain a finishing liquid, and the hydrophilic polyester fabric is dipped and rolled twice in the finishing liquid to obtain a preliminary finished fabric; a polyurethane finishing agent is dispersed in ethyl acetate to obtain a secondary finishing liquid, and the preliminary finished fabric is dipped and rolled twice in the secondary finishing liquid to obtain a sweat-free and ammonia-free elastic polyester.
[0023] The sweat-free and spandex-free polyester fiber prepared according to the above steps has good moisture absorption and perspiration removal properties and hydrophobic and stain-resistant properties.
[0024] In summary, the present application includes at least one of the following beneficial technical effects: 1. Hydrophilic polyester fiber improves the problem of poor moisture absorption of traditional polyester. By introducing hydrophilic groups, it can quickly absorb sweat discharged from the human body, keeping the skin dry and comfortable at all times, greatly improving the comfort of wearing; the moisture wicking finishing agent works synergistically with the hydrophilic polyester fiber to efficiently absorb moisture and promote the rapid diffusion and evaporation of sweat, prevent sweat residue, reduce bacterial growth and odor generation, and reduce the appearance of sweat marks; the polyurethane finishing agent can cross-link with the fabric fiber, and cover the film layer on the basis of the moisture wicking finishing agent, further improving the durability and stability of sweat-free and spandex-free polyester, making the fabric smooth and comfortable; through the synergistic effect of hydrophilic polyester fiber, moisture wicking finishing agent and polyurethane finishing agent, the moisture wicking performance of polyester is effectively improved, the appearance of sweat marks is reduced, and the beauty and comfort of wearing are improved.
[0025] 2. Citric acid molecules contain multiple carboxyl and hydroxyl groups, which can form hydrogen bonds with water molecules to enhance the hydrophilicity of the fiber; polyethylene glycol molecular chains are rich in ether bonds, which can form hydrogen bonds with water molecules, thus giving the fiber good hygroscopicity. The fiber can quickly absorb sweat and keep the skin surface dry; the sulfonic acid group in sodium 5-sulfoisophthalate provides ionicity for the fiber, increases the affinity of the fiber for water molecules, and can form a hydration layer through ionic interactions, further improving the fiber's moisture absorption capacity. Sweat is quickly conducted to the fiber surface through the capillary action between the fibers, accelerating the evaporation of sweat, thereby improving the moisture absorption and perspiration performance.
[0026] 3. N, N-diethyl-2-acrylamide has an amide group, has good hydrophilicity and temperature sensitivity, can undergo a conformational transformation when the temperature rises, becoming more hydrophilic, and repellent at low temperatures, thereby improving the moisture absorption and perspiration resistance of the fabric and wearing comfort; the trifluoroethyl group of trifluoroethyl methacrylate has low surface energy, which can improve the hydrophobic and stain-resistant properties of the fabric, thereby improving wearing comfort; vinyl tri(β-methoxyethoxy) silane has a volume-increasing effect, and the siloxane structure can condense with the hydroxyl groups on the fiber surface after hydrolysis, thereby enhancing the bonding force between the moisture absorption and perspiration finishing agent and the fiber surface, thereby improving the stability and durability of the sweat-free and spandex-free polyester. DETAILED DESCRIPTION
[0027] The present application discloses a sweat-free, non-spandex polyester and a preparation method thereof. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the embodiments: Raw materials description: citric acid (CAS No.: 77-92-9), polyethylene glycol is PEG-400 (CAS No.: 25322-68-3), catalyst is monobutyltin oxide (CAS No.: 2273-43-0), thermal stabilizer is triphenyl phosphite (CAS No.: 101-02-0), sodium 5-sulfonate isophthalic acid (CAS No.: 6362-79-4), tetrabutylammonium bromide (CAS No.: 1643-19-2), N, N-diethyl-2-acrylamide (CAS No.: 2675-94-7), trifluoroethyl methacrylate (CAS No.: 352-87-4), vinyl tris (β-methoxyethoxy) silane (CAS No.: 1067 -53-4), azobisisobutyronitrile (CAS No.: 78-67-1), styrene (CAS No.: 100-42-5), stabilizer is polyvinyl pyrrolidone (CAS No.: 9003-39-8), n-octadecane (CAS No.: 593-45-3), hexadecyltrimethylammonium bromide (CAS No.: 57-09-0), tetrabutyl titanate (CAS No.: 5593-70-4), the model of polyurethane finishing agent is MCH-513, purchased from Wuxi Yicheng Chemical Co., Ltd., terephthalic acid (CAS No.: 100-21-0), isophthalic acid (CAS No.: 121-91-5), moisture wicking finishing agent SW was purchased from Beijing Jieershuang High-tech Co., Ltd.
[0028] Example 1 Preparation of hydrophilic polyester fibers 0.14 kg of citric acid, 5.97 kg of polyethylene glycol and 0.05 kg of catalyst were heated to melt to obtain a molten mixture, and stirring was started at a rate of 200 rpm. After keeping warm for 1 hour, 0.08 kg of heat stabilizer was added, and the temperature was raised to 240 ° C at a rate of 12 ° C / h for reaction for 2 hours, water was evaporated, and the temperature was kept warm for 1 hour, then cooled to 180 ° C, 1 L of xylene and 3.89 kg of sodium 5-sulfonate of isophthalic acid were added, and the temperature was raised to 240 ° C again for reaction for 2 hours, and then the reduced pressure distillation reaction was carried out at a constant temperature. After the acid value of the system is less than 8.0, the temperature was lowered to below 30 ° C to discharge the material to obtain a hydrophilic polyester.
[0029] The hydrophilic polyester prepared above and 0.5 kg of tetrabutylammonium bromide were dispersed in 40 L of N, N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrostatic spinning with a spinning voltage of 30 kV, a receiving distance of 15 cm, a syringe propulsion rate of 0.005 mm / s, and an inner diameter of the nozzle of 0.5 mm to obtain a hydrophilic polyester fiber.
[0030] Preparation of moisture wicking finishing agent 0.57 kg of N, N-diethyl-2-acrylamide, 0.15 kg of trifluoroethyl methacrylate and 0.28 kg of vinyl tri(β-methoxyethoxy)silane were mixed and dispersed in anhydrous ethanol, and 10 g of azobisisobutyronitrile was added after nitrogen was passed for 30 minutes. The temperature was raised to 80° C. and reacted for 6 hours. The surface modifier was obtained after cooling to below 30° C.
[0031] 0.75 kg of styrene, 0.25 kg of stabilizer, 0.75 kg of n-octadecane and 50 g of azobisisobutyronitrile were mixed and dispersed, added into 25 L of deionized water, and homogenized to obtain an emulsion; nitrogen was passed through the emulsion for 30 min, the temperature was raised to 75°C, and the reaction was carried out at a speed of 200 rpm for 8 h. After the reaction was completed, the emulsion was washed with petroleum ether and filtered to obtain single-layer microcapsules.
[0032] The single-layer microcapsules prepared above and 0.2 kg of hexadecyltrimethylammonium bromide were dispersed in 10 L of 80% ethanol aqueous solution, and ultrasonicated for 30 min to obtain a dispersion liquid. 0.5 L of 0.1 mol / L ammonium carbonate solution was added to the dispersion liquid to obtain a dispersion reaction liquid. 1 kg of tetrabutyl titanate was dispersed in 5 L of anhydrous ethanol to obtain a precursor solution. The precursor solution and the dispersion reaction liquid were mixed, stirred at 35 ° C and 200 rpm for 8 h, and washed after centrifugation to obtain double-layer microcapsules.
[0033] 1 kg of double-layer microcapsules and 0.5 kg of surface modifier were dispersed in 5 L of anhydrous ethanol, stirred at 40° C. and 200 rpm for 8 h, filtered and dried in an oven at 60° C. to obtain a moisture wicking finishing agent.
[0034] Preparation of sweat-free and non-spandex polyester The hydrophilic polyester fiber was woven to obtain a hydrophilic polyester fabric, 0.5 kg of moisture absorption and perspiration finishing agent was dispersed in deionized water to obtain a finishing liquid, 4 kg of hydrophilic polyester fabric was twice dipped and twice rolled in the finishing liquid, with a bath ratio of 1:20, to obtain a preliminary finished fabric; 0.4 kg of polyurethane finishing agent was dispersed in ethyl acetate to obtain a secondary finishing liquid, the preliminary finished fabric was twice dipped and twice rolled in the secondary finishing liquid, with a bath ratio of 1:30, to obtain a sweat-free and ammonia-free elastic polyester.
[0035] Example 2 Preparation of hydrophilic polyester fibers 0.28 kg of citric acid, 5.89 kg of polyethylene glycol and 0.05 kg of catalyst were heated to melt to obtain a molten mixture, and stirring was started at a rate of 200 rpm. After keeping warm for 1 hour, 0.08 kg of heat stabilizer was added, and the temperature was raised to 240 ° C at a rate of 12 ° C / h for reaction for 2 hours, water was evaporated, and the temperature was kept warm for 1 hour, then cooled to 180 ° C, 1 L of xylene and 3.83 kg of sodium 5-sulfonate of isophthalic acid were added, and the temperature was raised to 240 ° C again for reaction for 2 hours, and then the reduced pressure distillation reaction was carried out at a constant temperature. After the acid value of the system is less than 8.0, the temperature was lowered to below 30 ° C to discharge the material to obtain a hydrophilic polyester.
[0036] The hydrophilic polyester prepared above and 0.5 kg of tetrabutylammonium bromide were dispersed in 40 L of N, N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrostatic spinning with a spinning voltage of 30 kV, a receiving distance of 15 cm, a syringe propulsion rate of 0.005 mm / s, and an inner diameter of the nozzle of 0.5 mm to obtain a hydrophilic polyester fiber.
[0037] Preparation of moisture wicking finishing agent 0.5 kg of N, N-diethyl-2-acrylamide, 0.26 kg of trifluoroethyl methacrylate and 0.24 kg of vinyl tri(β-methoxyethoxy)silane were mixed and dispersed in anhydrous ethanol, and 10 g of azobisisobutyronitrile was added after nitrogen was passed for 30 minutes. The temperature was raised to 80° C. and reacted for 6 hours. The surface modifier was obtained after cooling to below 30° C.
[0038] 0.75 kg of styrene, 0.25 kg of stabilizer, 0.75 kg of n-octadecane and 50 g of azobisisobutyronitrile were mixed and dispersed, added into 25 L of deionized water, and homogenized to obtain an emulsion; nitrogen was passed through the emulsion for 30 min, the temperature was raised to 75°C, and the reaction was carried out at a speed of 200 rpm for 8 h. After the reaction was completed, the emulsion was washed with petroleum ether and filtered to obtain single-layer microcapsules.
[0039] The single-layer microcapsules prepared above and 0.2 kg of hexadecyltrimethylammonium bromide were dispersed in 10 L of 80% ethanol aqueous solution, and ultrasonicated for 30 min to obtain a dispersion liquid. 0.5 L of 0.1 mol / L ammonium carbonate solution was added to the dispersion liquid to obtain a dispersion reaction liquid. 1 kg of tetrabutyl titanate was dispersed in 5 L of anhydrous ethanol to obtain a precursor solution. The precursor solution and the dispersion reaction liquid were mixed, stirred at 35 ° C and 200 rpm for 8 h, and washed after centrifugation to obtain double-layer microcapsules.
[0040] 1 kg of double-layer microcapsules and 0.5 kg of surface modifier were dispersed in 5 L of anhydrous ethanol, stirred at 40° C. and 200 rpm for 8 h, filtered and dried in an oven at 60° C. to obtain a moisture wicking finishing agent.
[0041] Preparation of sweat-free and non-spandex polyester The hydrophilic polyester fiber was woven to obtain a hydrophilic polyester fabric, 0.8 kg of moisture absorption and perspiration finishing agent was dispersed in deionized water to obtain a finishing liquid, 6 kg of hydrophilic polyester fabric was twice dipped and twice rolled in the finishing liquid, with a bath ratio of 1:20, to obtain a preliminary finished fabric; 0.6 kg of polyurethane finishing agent was dispersed in ethyl acetate to obtain a secondary finishing liquid, the preliminary finished fabric was twice dipped and twice rolled in the secondary finishing liquid, with a bath ratio of 1:30, to obtain a sweat-free and ammonia-free elastic polyester.
[0042] Example 3 Preparation of hydrophilic polyester fibers 0.21 kg of citric acid, 5.93 kg of polyethylene glycol and 0.05 kg of catalyst were heated to melt to obtain a molten mixture, and stirring was started at a rate of 200 rpm. After keeping warm for 1 hour, 0.08 kg of heat stabilizer was added, and the temperature was raised to 240 ° C at a rate of 12 ° C / h for reaction for 2 hours, water was evaporated, and the temperature was kept warm for 1 hour, then the temperature was lowered to 180 ° C, 1 L of xylene and 3.86 kg of sodium 5-sulfonate of isophthalic acid were added, and the temperature was raised to 240 ° C again for reaction for 2 hours, and then the reduced pressure distillation reaction was carried out at a constant temperature. After the acid value of the system is less than 8.0, the temperature was lowered to below 30 ° C to discharge the material to obtain a hydrophilic polyester.
[0043] The hydrophilic polyester prepared above and 0.5 kg of tetrabutylammonium bromide were dispersed in 40 L of N, N-dimethylformamide to obtain a spinning solution, and the spinning solution was subjected to electrostatic spinning with a spinning voltage of 30 kV, a receiving distance of 15 cm, a syringe propulsion rate of 0.005 mm / s, and an inner diameter of the nozzle of 0.5 mm to obtain a hydrophilic polyester fiber.
[0044] Preparation of moisture wicking finishing agent 0.53 kg of N, N-diethyl-2-acrylamide, 0.21 kg of trifluoroethyl methacrylate and 0.26 kg of vinyl tri(β-methoxyethoxy)silane were mixed and dispersed in anhydrous ethanol, and 10 g of azobisisobutyronitrile was added after nitrogen was passed for 30 minutes. The temperature was raised to 80° C. and reacted for 6 hours. The surface modifier was obtained after cooling to below 30° C.
[0045] 0.75 kg of styrene, 0.25 kg of stabilizer, 0.75 kg of n-octadecane and 50 g of azobisisobutyronitrile were mixed and dispersed, added into 25 L of deionized water, and homogenized to obtain an emulsion; nitrogen was passed through the emulsion for 30 min, the temperature was raised to 75°C, and the reaction was carried out at a speed of 200 rpm for 8 h. After the reaction was completed, the emulsion was washed with petroleum ether and filtered to obtain single-layer microcapsules.
[0046] The single-layer microcapsules prepared above and 0.2 kg of hexadecyltrimethylammonium bromide were dispersed in 10 L of 80% ethanol aqueous solution, and ultrasonicated for 30 min to obtain a dispersion liquid. 0.5 L of 0.1 mol / L ammonium carbonate solution was added to the dispersion liquid to obtain a dispersion reaction liquid. 1 kg of tetrabutyl titanate was dispersed in 5 L of anhydrous ethanol to obtain a precursor solution. The precursor solution and the dispersion reaction liquid were mixed, stirred at 35 ° C and 200 rpm for 8 h, and washed after centrifugation to obtain double-layer microcapsules.
[0047] 1 kg of double-layer microcapsules and 0.5 kg of surface modifier were dispersed in 5 L of anhydrous ethanol, stirred at 40° C. and 200 rpm for 8 h, filtered and dried in an oven at 60° C. to obtain a moisture wicking finishing agent.
[0048] Preparation of sweat-free and non-spandex polyester The hydrophilic polyester fiber was woven to obtain a hydrophilic polyester fabric, 0.65 kg of moisture absorption and perspiration finishing agent was dispersed in deionized water to obtain a finishing liquid, 5 kg of hydrophilic polyester fabric was twice dipped and twice rolled in the finishing liquid, with a bath ratio of 1:20, to obtain a preliminary finished fabric; 0.5 kg of polyurethane finishing agent was dispersed in ethyl acetate to obtain a secondary finishing liquid, the preliminary finished fabric was twice dipped and twice rolled in the secondary finishing liquid, with a bath ratio of 1:30, to obtain a sweat-free and ammonia-free elastic polyester.
[0049] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that in Example 4, the amount of citric acid used is 0.07 kg, the amount of polyethylene glycol used is 6.02 kg, and the amount of 5-sodium sulfoisophthalate used is 3.91 kg.
[0050] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that in Example 5, the amount of citric acid used is 0.35 kg, the amount of polyethylene glycol used is 5.85 kg, and the amount of 5-sodium sulfoisophthalate used is 3.8 kg.
[0051] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, citric acid is replaced by terephthalic acid when preparing the hydrophilic polyester fiber.
[0052] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that in Example 7, 5-sodium sulfonate is replaced by isophthalic acid when preparing the hydrophilic polyester fiber.
[0053] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that tetrabutylammonium bromide is not added when preparing the hydrophilic polyester fiber in Example 8.
[0054] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the amount of N,N-diethyl-2-acrylamide used is 0.61 kg, the amount of trifluoroethyl methacrylate used is 0.09 kg, and the amount of vinyl tri(β-methoxyethoxy)silane used is 0.3 kg.
[0055] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that in Example 10, the amount of N,N-diethyl-2-acrylamide is 0.47 kg, the amount of trifluoroethyl methacrylate is 0.31 kg, and the amount of vinyl tri(β-methoxyethoxy)silane is 0.22 kg.
[0056] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that trifluoroethyl methacrylate is not added when preparing the surface modifier in Example 11.
[0057] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, no vinyl tris(β-methoxyethoxy)silane is added when preparing the surface modifier.
[0058] Example 13 Example 13 is based on Example 3. The only difference between Example 13 and Example 3 is that tetrabutyl titanate is not added to the wall material when the moisture absorbing and perspiration-releasing finishing agent is prepared in Example 13.
[0059] Comparative Example 1 Comparative Example 1 is based on Example 3, and the only difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, the hydrophilic polyester fiber is replaced by polyethylene terephthalate fiber.
[0060] Comparative Example 2 Comparative Example 2 is based on Example 3, and the only difference between Comparative Example 2 and Example 3 is that the moisture absorption and perspiration finishing agent in Comparative Example 2 is replaced by moisture absorption and perspiration finishing agent SW.
[0061] Comparative Example 3 Comparative Example 3 is based on Example 3, and the only difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, no polyurethane finishing agent is used for secondary finishing.
[0062] Performance testing (1) GB / T 21655.1-2023 Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method was selected as the standard to test the water absorption, wicking height, evaporation rate and moisture permeability of the test samples. Three samples were prepared for each sample, and the average value was taken after measurement. The results are recorded in Table 1.
[0063] (2) Water contact angle test: The contact angles at water temperatures of 20°C and 40°C were tested respectively. Each sample was tested three times and the average value was taken after measurement. The results are recorded in Table 1.
[0064] Table 1 Test results As shown in Table 1, the water absorption rate of Examples 1-3 is greater than 86%, the wicking height is greater than 92 mm / 30 min, the evaporation rate is greater than 0.21 g / h, and the moisture permeability is greater than 8653 g / (m 2 ·24h), the water contact angle at 20°C is greater than 121.3°, and the water contact angle at 40°C is less than 34.2°, which shows that the sweat-free and non-spandex polyester prepared in the present application has good moisture absorption and perspiration performance and hydrophobic and stain-resistant properties.
[0065] As can be seen from Table 1, the only difference between Examples 4, 5, 6, 7, 8, and Comparative Example 1 and Example 3 is that in Example 4, the mass ratio of citric acid, polyethylene glycol, and 5-sodium sulfoisophthalate is 0.012:1:0.65, in Example 5, the mass ratio of citric acid, polyethylene glycol, and 5-sodium sulfoisophthalate is 0.06:1:0.65, in Example 6, citric acid is replaced by terephthalic acid when preparing the hydrophilic polyester fiber, in Example 7, 5-sodium sulfoisophthalate is replaced by isophthalic acid when preparing the hydrophilic polyester fiber, in Example 8, tetrabutylammonium bromide is not added when preparing the hydrophilic polyester fiber, in Comparative Example 1, the hydrophilic polyester fiber is replaced by polyethylene terephthalate fiber, in Examples 4, 5, 6, 7, and 8 have reduced moisture absorption and perspiration performance compared with Example 3; this is because if the mass ratio of citric acid, polyethylene glycol, and 5-sodium sulfonate of isophthalic acid is not within the specified range, too much or too little citric acid will affect the moisture absorption and perspiration performance and the stability of polyester; if citric acid is replaced by terephthalic acid, or 5-sodium sulfonate of isophthalic acid is replaced by isophthalic acid, the introduction of hydrophilic groups is lacking, and the moisture absorption and perspiration performance is reduced; if tetrabutylammonium bromide is not added, the hydrophilic polyester fiber lacks a branching structure, the porosity is reduced, and the moisture absorption and perspiration performance is reduced; if the hydrophilic polyester fiber is replaced by polyethylene terephthalate fiber, the introduction of hydrophilic groups and the design of branching structures are lacking, and the moisture absorption and perspiration performance is reduced.
[0066] As shown in Table 1, the only difference between Examples 9, 10, 11, 12, and 13 and Example 3 is that the mass ratio of N, N-diethyl-2-acrylamide, trifluoroethyl methacrylate, and vinyl tri(β-methoxyethoxy)silane in Example 9 is 1:0.15:0.48, the mass ratio of N, N-diethyl-2-acrylamide, trifluoroethyl methacrylate, and vinyl tri(β-methoxyethoxy)silane in Example 10 is 1:0.65:0.48, and the surface modifier in Example 11 is not used. Trifluoroethyl methacrylate was added, vinyl tri(β-methoxyethoxy) silane was not added when preparing the surface modifier in Example 12, tetrabutyl titanate was not added to the wall material when preparing the moisture wicking finishing agent in Example 13, and the moisture wicking finishing agent was replaced with the moisture wicking finishing agent SW in Comparative Example 2. Compared with Examples 9, 10, 11, 12, 13, and Comparative Example 2 and Example 3, the moisture wicking performance and the hydrophobic stain resistance performance were all reduced; this is because if N, N-diethyl-2-acrylamide, trifluoroethyl methacrylate The mass ratio of trifluoroethyl methacrylate to vinyl tri(β-methoxyethoxy) silane is not within the specified range. Too much or too little trifluoroethyl methacrylate will affect the surface energy and stability of the surface modifier, thereby affecting the moisture absorption and perspiration resistance and hydrophobic stain resistance. If trifluoroethyl methacrylate is not added, the surface energy will increase, the stability will decrease, and the moisture absorption and perspiration resistance and hydrophobic stain resistance will decrease. If vinyl tri(β-methoxyethoxy) silane is not added, the reactivity and adhesion of the surface modifier to the wall material will decrease, and the stability of the moisture absorption and perspiration finishing agent will decrease. The moisture absorption and perspiration performance and the hydrophobic and stain resistance performance are reduced; without adding tetrabutyl titanate, there is a lack of further reinforcement and antioxidant protection of titanium dioxide, and the stability of the moisture absorption and perspiration finishing agent is reduced, thereby the moisture absorption and perspiration performance and the hydrophobic and stain resistance performance are reduced; in Comparative Example 2, the moisture absorption and perspiration finishing agent is replaced with the moisture absorption and perspiration finishing agent SW, there is a lack of phase change material temperature regulation to promote the evaporation of sweat, there is no temperature-sensitive compound to undergo conformational transformation at an appropriate temperature, the stability of the fabric is reduced, the moisture absorption and perspiration effect is greatly reduced, and the hydrophobic and stain resistance performance is also affected.
[0067] As can be seen from Table 1, the only difference between Comparative Example 3 and Example 3 is that no polyurethane finishing agent is used for secondary finishing in Comparative Example 3, and compared with Example 3, the moisture absorption and perspiration removal performance and the hydrophobic and stain resistance performance of Comparative Example 3 are reduced; this is because no polyurethane finishing agent is used for secondary finishing, lacks the protection of surface film formation, the stability of the sweat-free and spandex-free polyester is reduced, and the moisture absorption and perspiration removal performance and the hydrophobic and stain resistance performance are deteriorated.
[0068] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A sweat-free, non-spandex polyester, characterized by: The raw materials for preparation include the following components in parts by weight: 4-6 parts of hydrophilic polyester fiber 0.5-0.8 parts of moisture wicking finishing agent 0.4-0.6 parts of polyurethane finishing agent.
2. The sweat-free and spandex-free polyester according to claim 1, characterized in that: The raw materials for preparing the hydrophilic polyester fiber include citric acid, polyethylene glycol and 5-sodium sulfonate of isophthalic acid.
3. The sweat-free and spandex-free polyester according to claim 2, characterized in that: The mass ratio of the citric acid, polyethylene glycol and sodium 5-sulfoisophthalate is (0.024-0.048):1:0.
65.
4. The sweat-free and spandex-free polyester according to claim 3, characterized in that: The hydrophilic polyester fiber is prepared by the following steps: The citric acid, polyethylene glycol and catalyst are heated until they are melted, and after obtaining a molten mixture, stirring is started, and a heat stabilizer is added after heat preservation, and the temperature is increased for reaction, and the water is evaporated and the temperature is maintained, and xylene and 5-sodium sulfoisophthalate are added after cooling, and the temperature is increased for reaction again, and then a vacuum distillation reaction is carried out at a constant temperature. After the reaction is completed, the temperature is reduced and the material is discharged to obtain a hydrophilic polyester; The hydrophilic polyester and tetrabutylammonium bromide prepared above are dispersed in N,N-dimethylformamide to obtain a spinning solution, and the spinning solution is subjected to electrostatic spinning to obtain hydrophilic polyester fibers.
5. The sweat-free and spandex-free polyester according to claim 1, characterized in that: The raw materials for preparing the moisture absorption and perspiration removal finishing agent include a surface modifier, a wall material and a core material.
6. The sweat-free, non-spandex polyester according to claim 5, characterized in that: The raw materials for preparing the surface modifier include N,N-diethyl-2-acrylamide, trifluoroethyl methacrylate and vinyl tri(β-methoxyethoxy)silane.
7. The sweat-free and spandex-free polyester according to claim 6, characterized in that: The mass ratio of the N,N-diethyl-2-acrylamide, trifluoroethyl methacrylate and vinyl tri(β-methoxyethoxy)silane is 1:(0.27-0.53):0.
48.
8. The sweat-free and spandex-free polyester according to claim 5, characterized in that: The raw materials for preparing the wall material include styrene and tetrabutyl titanate.
9. The sweat-free and spandex-free polyester according to claim 5, characterized in that: The core material includes n-octadecane.
10. A method for preparing the sweat-free and spandex-free polyester as claimed in any one of claims 1 to 9, characterized in that: The steps include: The hydrophilic polyester fiber is woven to obtain a hydrophilic polyester fabric, a moisture absorption and perspiration-releasing finishing agent is dispersed in deionized water to obtain a finishing liquid, and the hydrophilic polyester fabric is dipped and rolled twice in the finishing liquid to obtain a preliminary finished fabric; a polyurethane finishing agent is dispersed in ethyl acetate to obtain a secondary finishing liquid, and the preliminary finished fabric is dipped and rolled twice in the secondary finishing liquid to obtain a sweat-free and ammonia-free elastic polyester.